Pengaruh Infill Type Hasil Cetak 3D Printer Terhadap Sifat Mekanik Material Berbahan Polylactic Acid (PLA) - Setiawan, Agris; Maharani, Intan; Probowati, Dyah (Fakultas Teknik UMSU, 2022)
The development of a quality product to get good results requires a technology, one of which is the use of 3D printing machines. One type of material that is most often used in the 3D Printer process is Polylactic acid (PLA). The results of the 3D Print must be carried out several tests, such as tensile, shrinkage, and flexural tests to find out how strong the specimen is to withstand the load that will be given. One of the factors that affect the tensile, shrinkage and flexural test results of the 3D Printer is the type of filler (pattern). Therefore, in this study, 3 types of tests will be carried out on variations in the infill type, namely triangle, concentric and gyroid. Specimen design was made using Autodesk Inventor software with reference to the standard dimensions of ASTM D638 Type IV for tensile testing of specimens and standard dimensions of ASTM D790 for flexural tests of specimens. Samples are characterized by using specimen code A, specimen B and specimen C. For example, specimen code A is the code for specimens with an infill gyroid, specimen B is a code for specimens with a concentric infill type and specimen code C is a code for specimens with an infill. triangle type. Results Based on the shrinkage measurements on the tensile test specimen and the flexural test specimen, it was found that specimen C had a fairly large shrinkage value compared to other specimens, namely 2.210.97% and 20.21%. The results of the tensile test also showed that specimen C had a higher ultimate tensile strength than the other specimens, which was 39.230.93 MPa. Based on the results of the flexural test that has been carried out, it can be seen that the highest flexural strength value is found in specimen C, which is 48.693.17 MPa. While the results of the porosity of the specimen showed that specimen C had a smaller porosity than the porosity of other specimens. Based on the 3 types of specimen variations, it can be said that specimen C has better strength and resistance values than other specimens.